Morphological differences of elite croatian female handball players according to their game position - Cizmek, A.; Ohnjec, K.; Vucetic, V.; Gruic, I. (Croatian Sports Medicine Journal, 2010)
This study presents morphologic characteristics of 37 elite Croatian female handball players. A set of 21 anthropometric measures was carried out on 12 wing attack players, 6 pivots, 6 goalkeepers and 13 back court players. Body fat percentage and BMI were also calculated. ANOVA showed statistically significant differences in variables of longitudinal skeletal dimensions, body volume and body fat. Post hoc analysis showed the most statistically significant differences in aforementioned variables between goalkeepers and wing attack players. Wing attack players are found to be with the lowest height and weight values, whereas goalkeepers are the tallest and the heaviest among all players according to their game position. Differences between wing attack players and back court players have been found in variables of longitudinal skeletal dimensions, thigh skinfold measures and upper leg and upper arm circumference, latter being the only variable of difference between wing attackers and pivot players.